High Volumetric Hydrogen Storage Capacity using Interpenetrated Metal–Organic Frameworks. Issue 3 (14th December 2017) - Balderas‐Xicohténcatl, Rafael; Schmieder, Phillip; Denysenko, Dmytro; Volkmer, Dirk; Hirscher, Michael
Abstract: Metal–organic frameworks with extremely large specific surface areas can reach very high gravimetric hydrogen storage capacities. However, these ultra‐porous materials possess typically a very low density and, therefore, a poor volumetric hydrogen storage capacity. Here we study experimentally the influence of interpenetration on the volumetric and gravimetric hydrogen storage capacity by comparing two metal–organic frameworks of the MFU‐4 family, non‐interpenetrated MFU‐4 l and CFA‐7 with an interpenetrated structure. At 77 K the absolute volumetric hydrogen uptake of CFA‐7 is more than twice that of MFU‐4 l . Abstract : Turning down the volume : Interpenetrated framework structures, which reduce the free volume in the large pores by wall material adsorbing hydrogen, have been proposed to improve the volumetric capacity more than a decade ago. Here the authors directly compare the gravimetric and volumetric hydrogen storage capacities using one non‐interpenetrated and one interpenetrated framework.